Development of a novel sodalite infiltrate for all-ceramic dental restorations / Ghassan Abdulhamid Naji - Ghassan , Abdulhamid Naji (2017)
The development of glass-infiltrated ceramic cores seems to be a promising technique to fabricate various fixed dental prostheses such as crowns and bridges. Various infiltrated materials have been developed to enhance the mechanical properties of these prostheses, but their effect on the opacity of all-ceramic systems is unclear. The current study aimed to develop a novel potassium bromide-sodalite (KBr-SOD) zeolite that could infiltrate into porous alumina and zirconia-toughened alumina (ZTA) frameworks under hydrothermal conditions, which can be used for all-ceramic fixed dental prostheses. The mechanical, thermal and aesthetic properties of the newly synthesised SOD zeolite-infiltrated core materials were evaluated and compared with the available In-Ceram core materials. The KBr-SOD zeolite was synthesised by in-situ hydrothermal process and infiltrated into the partially-sintered alumina and ZTA frameworks prior to sintering at 1600 °C for densification. The two test groups investigated were sodalite zeolite-infiltrated alumina (IA-SOD) and sodalite zeolite-infiltrated ZTA (IZ-SOD), while the control groups were glass-infiltrated alumina (IA-glass) and glass-infiltrated ZTA (IZ-glass) (In-Ceram, Vita Zahnfabrik, Bad Säckingen, Germany). All samples were characterised for their mechanical properties such as biaxial flexural strength, microhardness, elastic modulus, fracture toughness and shear bond strength. For optical properties, relative translucency and brightness were evaluated while for thermal properties, the coefficient of thermal expansion was measured. Qualitative analysis of the resulting materials was also performed using scanning electron microscopy coupled with energy dispersive X-ray spectroscopy whereas X-ray diffraction was carried out to confirm the crystallinity and phases of the samples. The present study showed the newly-developed SOD-infiltrated samples had superior mechanical, thermal and optical properties compared to the control groups. For both IZ-SOD and IA-SOD samples, the biaxial flexural strength values were 324.70 MPa and 233.60 MPa respectively, which were lower than the control groups. However, these values exceeded the required value of 100–150 MPa as specified by ISO 6872:2015. For the fracture toughness, IZ-SOD and IA-SOD also exhibited higher than the required value of 2.5–3.5 MPa m1/2 as specified by British Standard (BSI, 6872, 2008) which were 4.95 MPa·m1/2 and 2.71 MPa·m1/2 respectively. Interestingly, the shear bond strength values obtained for both IZ-SOD and IA-SOD were 26.83 MPa and 24.91 MPa respectively, indicating favourable bonding at core/veneer interface. Moreover, the CTE values for both IZ-SOD and IA-SOD samples were 8.62 × 10-6 K-1 and 8.37 × 10-6 K-1 respectively, which were statistically higher than the control groups. The translucency and brightness of IA-SOD samples were 0.70 and 88.25 respectively, which were significantly higher than all the other groups (p<0.001). The newly-developed SOD zeolite-infiltrated frameworks exhibited properties of a potential alternative to ceramic substructure core materials and can be considered more suitable for anterior teeth restorations. Furthermore, the synthesis of the SOD zeolite is simple and cheap and the use of a rare-earth heavy metal such as lanthanum oxide can be avoided.